All Days 2005
DOI: 10.2118/111051-ms
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface Fracture Analysis in Carbonate Reservoirs: Kohat/Potwar Plateau, North Pakistan

Abstract: Carbonate reservoirs in Northern Pakistan are characterized by tight limestone.In these reservoirs, fractures are important for production and reservoirmodeling. This paper addresses problems related to subsurface fracture analysisbased mainly on image logs. Natural fractures occur as systematic and unsystematic sets of definite andrandom orientation respectively. The subsurface analysis of fractures useselectrical and acoustic image logs to characterize fractures as either naturalor induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…Similar reservoirs are common elsewhere in the Potwar fold-and-thrust belt (Jadoon et al, 2003;Jadoon et al, 2007;Hasany et al, 2019) and fracture permeability is reported to attain 5 D in some fields. In these types of reservoirs, it is necessary to have a high fracture intensity or high fracture porosity for the reservoir to be economically viable.…”
Section: Ratana Field Carbonate Reservoirssupporting
confidence: 54%
See 2 more Smart Citations
“…Similar reservoirs are common elsewhere in the Potwar fold-and-thrust belt (Jadoon et al, 2003;Jadoon et al, 2007;Hasany et al, 2019) and fracture permeability is reported to attain 5 D in some fields. In these types of reservoirs, it is necessary to have a high fracture intensity or high fracture porosity for the reservoir to be economically viable.…”
Section: Ratana Field Carbonate Reservoirssupporting
confidence: 54%
“…In the Wargal Formation in Ratana-4, a total of 54 steeply inclined open-mode fractures were recorded over an interval of ~120 m, although most of these were developed in a cleaner limestone interval which was only ~30 m thick and are therefore likely to be part of a separate fracture system. Some constraints on the fracture networks and their timing can be gained from studies of related outcrops and adjacent fields (Guilhaumou et al, 2004;Jadoon et al, 2007;Ali-Shah et al, 2008;Dasti et al, 2018). The Sakesar and Chorgali Formations are exposed in Chorgali Pass, some 30 km west of the Ratana field, where the steeply dipping Khari-Murat thrust brings these carbonate units to the surface from a depth of 5 km in a very short lateral distance (Kamran and Siddiqi, 2011; see Fig.…”
Section: Fracture Network In the Ratana Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Strata-bound [2] type of fractures are present in this facie. It consists of argillaceous limestone with well developed bedding features.…”
Section: Facie-dmentioning
confidence: 89%
“…The phenomenon of fracturing is related with the folding of the Meyal anticlinal structure given in Fig. 16, proposed by Jadoon et al (2005).…”
Section: Thermal Maturity Modellingmentioning
confidence: 99%